Family Studies of Patients with Reduced Ristocetin Aggregation and Abnormalities of Factor VIII and/or Platelet Function - Ekert, H; Ananthakrishnan, R; Muntz, R. H; Dowling, S; D’Souza, S (Thrombosis and Haemostasis, 1976)
Factor VIII procoagulant activity (VIIIc), antigen (vWa), mobility of the antigen on two dimensional Immunoelectrophoresis and platelet function were studied in 9 families with reduced ristocetin induced platelet aggregation rate (RIPA) and/or deficiency of plasma factor(s) required for ristocetin aggregation of washed normal platelets (vWf). The families could be subdivided into 4 groups. Group I showed dominant inheritance and reduced levels of VIIIc and vWa characteristic of typical von Willebrand’s disease. All patients had reduced vWf and in 7 of 10 RIPA was reduced. Group II showed normal levels of VIIIc but reduced vWa. All showed reduced vWf but RIPA was reduced in one patient only. There was a good correlation between vWf and vWa and VIIIc in both groups. The bleeding time correlated with vWf in group I but not group II. Group III showed normal or nearly normal VIIIc and vWa but there was an increased mobility of vWa compared to normals and to groups I and II. RIPA was markedly reduced as was the vWf in one patient. Group IV is represented by one child with a strong family history of bleeding, who had reduced RIPA and defective platelet release reaction. The vWf in this child was normal and the ratio between VIIIc and vWa was similar to that seen in carriers of haemophilia. This spectrum of abnormalities of ristocetin aggregation justifies the use of the term ‘von Willebrand’s syndrome’.